2009
DOI: 10.1007/s11259-009-9226-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of faecal culture and IS900 PCR assay for the detection of Mycobacterium avium subsp. paratuberculosis in bovine faecal samples

Abstract: Comparative efficacy of faecal culture and IS900 Polymerase chain reaction (PCR) assay of faecal samples was investigated in 40 clinically suspected cases of Johne's disease in dairy cattle. The sensitivity of faecal culture and PCR assay in this study was 52.5% (21/40) and 90% (36/40) respectively. All isolates appeared only on the mycobactin J supplemented Herrold's egg yolk medium (HEYM) at 8-16 weeks post-inoculation, were acid-fast and were positive for IS900 PCR yielding a single amplicon of 217 bp. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 31 publications
1
17
1
2
Order By: Relevance
“…Em certos casos, os fragmentos específicos com localização definida no genoma, podem ser utilizados em estudos epidemiológicos como marcador para identificação de espécies ou diferenciação entre as cepas de microrganismos (Dombek et al 2000). A presença de múltiplas cópias desta sequência no cromossomo do Map eleva a sensibilidade dos testes quando comparados com testes que utilizam como alvos os fragmentos genéticos únicos (Li et al 2005, Sohal et al 2009, Soumya et al 2009, Imirzalioglu et al 2011. Além do IS900, tem sido utilizado o IS1311 (Sohal et al 2009, Timms et al 2011, o F57, sequencia subspécie específica (Green et al 1989, Poupart et al 1993 Kralik et al 2011, Timms et al 2011) , o alvo 251 (Rajeev et al 2005, ISMAP02 (Paustian et al 2004, Li et al 2005, Stabel & Bannantine 2005, ISMav2 (Strommenger et al 2001, Schonenbrucher et al 2008, o gene hspX (Schonenbrucher et al 2008) e "open reading frames" (ORFs) MAP0865 e MAP2765c (Imirzalioglu et al 2011), sequencias que podem ser considerados instrumentos valiosos para otimizar a especificidade de testes diagnósticos.…”
Section: Biologia Molecularunclassified
“…Em certos casos, os fragmentos específicos com localização definida no genoma, podem ser utilizados em estudos epidemiológicos como marcador para identificação de espécies ou diferenciação entre as cepas de microrganismos (Dombek et al 2000). A presença de múltiplas cópias desta sequência no cromossomo do Map eleva a sensibilidade dos testes quando comparados com testes que utilizam como alvos os fragmentos genéticos únicos (Li et al 2005, Sohal et al 2009, Soumya et al 2009, Imirzalioglu et al 2011. Além do IS900, tem sido utilizado o IS1311 (Sohal et al 2009, Timms et al 2011, o F57, sequencia subspécie específica (Green et al 1989, Poupart et al 1993 Kralik et al 2011, Timms et al 2011) , o alvo 251 (Rajeev et al 2005, ISMAP02 (Paustian et al 2004, Li et al 2005, Stabel & Bannantine 2005, ISMav2 (Strommenger et al 2001, Schonenbrucher et al 2008, o gene hspX (Schonenbrucher et al 2008) e "open reading frames" (ORFs) MAP0865 e MAP2765c (Imirzalioglu et al 2011), sequencias que podem ser considerados instrumentos valiosos para otimizar a especificidade de testes diagnósticos.…”
Section: Biologia Molecularunclassified
“…IS900 has been demonstrated to be a useful target for PCR amplification to aid in the diagnosis of M. avium subsp. paratuberculosis in biological samples (24,(27)(28)(29). Although IS900-like sequences are found in other bacteria (30,31), the stringent selection of IS900-like specific primers avoids the amplification of IS900-like elements (32).…”
mentioning
confidence: 99%
“…Earlier studies had also reported endemicity of MAP infection in domestic livestock using microscopy (39.3-68.5%), ELISA (29.0-92.3%), blood PCR (13.1%) and fecal culture (52.5%) (Singh et al, 2013b;Soumya et al, 2009;Vinodh Kumar et al, 2011). Due to poor sensitivity, specificity and non-availability of Johnin, (Singh et al, 2014b;Wadhwa et al, 2012), therefore, three tests were used in the present study to investigate status of BJD in the clinically infected cows.…”
Section: Discussionmentioning
confidence: 92%